Implementation of Early Recovery After Caesarean Surgery Protocol in Floating Hospital (Case Series) - Akhyar Nur Uhud; Berta Welantika; Senda Sulvain Rahmaningrat; Talitha Yuliaputri Aden (Ikatan Dokter Indonesia Wilayah Jawa Timur, 2023)
Introduction: Enhanced Recovery After Caesarean Surgery (ERACS) is a new concept that combines various evidence-based perioperative care to reduce post-operative complications and accelerate patient recovery after Caesarean Surgery (C-Section). The advantages of the ERACS Protocol, including accelerating patients' recoveries, shortening hospital stays, and reducing post-operative complications, make it suitable to be applied in floating hospitals. The problem is whether this protocol can be applied if it is carried out in a floating hospital with all its limitations. We would like to present our case series with modified ERACS protocol in Floating Hospital Ksatria Airlangga. Case Presentation: We present 4 patients scheduled for elective C-Section. Neuraxial opioids with low-dose morphine, the most frequently used technique in ERACS, were not administered due to its unavailability in Ksatria Airlangga Floating Hospital. We provide pre-emptive analgesia and multimodal analgesia to obtain adequate perioperative analgesia. All patients were admitted to the nearest public health centre for post-operative observation and discharged after 1 to 2 days. Satisfaction was achieved in all patients without any significant postoperative complications. Conclusion: The ERACS protocols’ main goal can be achieved even under limited conditions, but several adjustments are required according to the available resources.